WOMEN OF KAZAKHSTAN. ENTERING THE AUTHORITIES - Шевченко, Л.Я.; Назарова, С.В. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2014)
The gender policy, breaking the existing traditional stereotype of the necessity for the social and political involvement of the woman only in successful solution of the family and youth problems, and children’s upbringing, is directed to the achieving the equality among the sexes, and to the change of views on the role and place of the woman in the society and politics.
Keywords: gender; power; women; politics